Key Aspects of Macroprudential Policy. (Policy Papers; Policy Paper, 2013)
The crisis has underscored the costs of systemic instability at both the national and the global levels and highlighted the need for dedicated macroprudential policies to achieve financial stability. Building on recent advances, this paper provides a framework to inform the IMF's country-specific advice on macroprudential policy. It recognizes that developing macroprudential policy is a work in progress, and addresses key issues to help ensure its effectiveness.